Hydroxyethyl cellulose-assisted hydrothermal synthesis of Bi 2S3 urchin-like colonies - Thongtem T. (2014)
Orthorhombic Bi2S3 with different morphologies was successfully synthesized by the acid-catalyst hydrothermal reactions of bismuth nitrate (Bi(NO3)3) and thiourea (NH2CSNH 2) solutions containing different amounts of hydroxyethyl cellulose (HEC). Phase, morphologies, and optical properties were characterized by X-ray diffraction, selected area electron diffraction, scanning and transmission electron microscopy, and ultraviolet-visible spectroscopy. The products, hydrothermally synthesized in the HEC-free, 0.25 g HEC-added, 0.5 g HEC-added and 1.00 g HEC-added solutions, were respectively proved to be orthorhombic Bi2S3 irregular nanorods, complete urchin-like colonies of regular nanorods, incomplete urchin-like colonies of regular nanorods, and highly crystalline regular nanorods growing along the [001] direction. Tauc band gaps of the orthorhombic Bi2S3 nanorods, synthesized in the HEC-free, 0.25 g HEC-added, and 1.00 g HEC-added solutions were determined to be 3.0, 1.75 and 1.8 eV, respectively. Formation mechanism of orthorhombic Bi2S3 nanorods, synthesized in the HEC-free and HEC-added solutions, was also discussed at great detail. © 2011 Elsevier B.V. All rights reserved.